DISCRIMINATION AGAINST MIGRANT WORKERS IN MALAYSIA - Muhammad Hafiz Badarulzaman; Zainal A Ayub; Zuryati M Yusoff; Harlida A Wahab (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractMigrant workers are often discriminated against in almost every aspect of life. Discrimination against them is due to irrational dislike of them and also negative perception towards them. It is alleged that migrant workers contribute to the crimes hike in Malaysia. Using doctrinal research methodology, this article discusses direct and perceptive discrimination against them. This article concludes that physical discriminations are mostly happened because ineffective enforcement of the law, abuse of powers and human-trafficking problem. Besides, migrant workers have not being major contributor to crime hike. Malaysia should introduce comprehensive migration law and strengthen the monitoring of recruitment agencies.